Pengembangan E-Worksheet Pembelajaran Biologi Berbasis Web Pada Materi Sistem Pencernaan - Muharam, Hariyadi; Ismail, Ismail; Karim, Hilda (Biology Teaching and Learning, 2018)
Abstract. Development of e-worksheet web-based in biological learning on the digestive system. Thesis. Biology Department. Mathematics and Science Faculty. State University of Makassar.The type of research used is research and development (R & D) which aims to develop learning media on web-based e-worksheet Biology using valid, practical Moodle on the digestive system material. The phase of research and development referred to Gall et al (2003) which consists of 5 steps, those are: (1) Preliminary study; (2) Planning (product design); (3) Preliminary development product; (4) Preliminary test and product revision (validation); (5) Final test and product revision (field test). The subjects’ research was 2 validators, 34 students of XI IPA5 SMAN 11 Makassar, and biology teacher of SMAN 11 Makassar. Data collection is done by testing product validity, collecting student and teacher response data. The collected data were analyzed using quantitative descriptive analysis, with the following results: (1) Validity received a valid category from 2 validators with value 4.80; (2) Teachers and students give a positive response to the product with value 4.27. Based on the results of the study, the learning media developed were declared valid and practice. Keywords: e-worksheet, validity, techer response and student response.